2015
DOI: 10.1371/journal.pone.0141474
|View full text |Cite
|
Sign up to set email alerts
|

5-HTTLPR Expression Outside the Skin: An Experimental Test of the Emotional Reactivity Hypothesis in Children

Abstract: BackgroundThere is increasing evidence that variation in the promoter region of the serotonin transporter gene SLC6A4 (i.e., the 5-HTTLPR polymorphism) moderates the impact of environmental stressors on child psychopathology. Emotional reactivity −the intensity of an individual’s response to other’s emotions− has been put forward as a possible mechanism underlying these gene-by-environment interactions (i.e., G×E). Compared to children homozygous for the L-allele (LL-genotypes), children carrying an S-allele (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 72 publications
0
9
2
Order By: Relevance
“…However, to our knowledge, this finding has not been replicated in school-aged children. Moreover, studies using related constructs such as fear and anger responses, as well as temperamental and observed emotional reactivity, found no associations with the 5-HTTLPR genotype (Auerbach et al, 2001;Dragan & Oniszczenko, 2005;Weeland, Slagt, et al, 2015) Our analyses did show other, unexpected, moderation findings: children's 5-HTTLPR genotype significantly moderated intervention effectiveness on parenting behavior, as well as the relation between observed positive parenting and child externalizing problems. Intervention effects on observed and reported negative parenting behavior, but not on parental affect or positive parenting behavior, were significantly moderated by children's 5-HTTLPR genotype.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…However, to our knowledge, this finding has not been replicated in school-aged children. Moreover, studies using related constructs such as fear and anger responses, as well as temperamental and observed emotional reactivity, found no associations with the 5-HTTLPR genotype (Auerbach et al, 2001;Dragan & Oniszczenko, 2005;Weeland, Slagt, et al, 2015) Our analyses did show other, unexpected, moderation findings: children's 5-HTTLPR genotype significantly moderated intervention effectiveness on parenting behavior, as well as the relation between observed positive parenting and child externalizing problems. Intervention effects on observed and reported negative parenting behavior, but not on parental affect or positive parenting behavior, were significantly moderated by children's 5-HTTLPR genotype.…”
Section: Discussioncontrasting
confidence: 68%
“…Changes in parental affect might be particularly important change mechanisms for children who show heightened arousability and behavioral responses to others’ emotions (i.e., heightened emotional reactivity). Specifically, temperamental negative affectivity and the serotonin transporter linked polymorphic region ( 5-HTTLPR ) polymorphism have been previously related to such individual differences in emotional reactivity and might be related constructs (Auerbach et al, 1999; Belsky & Pluess, 2009; Weeland, Slagt, et al, 2015). The current study tested whether intervention-induced changes in observed parental affect as well as observed and reported positive and negative parenting behavior mediated the effects of the BPT program the Incredible Years (IY) on parent-reported child externalizing problems.…”
mentioning
confidence: 99%
“…Physiological measures might include hormonal and/or sympathetic and parasympathetic nervous system stress markers [ 53 ]; relevant temperamental characteristics could include emotion regulation abilities [ 54 ] or approach avoidance tendencies [ 55 ]. Indeed, the short/long 5HTTLPR polymorphism has been associated with individual differences in epigenetic methylation [ 56 ], stress physiology [ 57 59 ], and temperament [ 60 , 61 ]. A combination of biological and behavioral markers could be used to identify meaningful subgroups and thus target interventions to those likely to respond.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that individuals' reactivity to environmental stimuli can be gauged on different levels: neurobiological, psychophysiological, and behavioral. For example, patterns of activity in brain areas [41,42], hostile reactivity in aversive family interactions [43], facial muscle tension, and respiratory sinus arrhythmia [44,45] may all be likely 'candidate endophenotypes' to include in our examinations of gene-by-parenting and temperament-by-parenting interactions in explaining variance in child externalizing behavior.…”
Section: Geertjan Overbeekmentioning
confidence: 99%